Designing Dormitory Student with Modern Architecture Concept at Universitas Sumatera Utara Kwala Bekala - Saragih, Sarah Nurdini; Amy Marisa (Jurnal Koridor, 2023)
Universitas Sumatera Utara Kuwala Bekala does not have student dormitory facilities, which is the main reason for this project. The application of modern architecture in dormitory buildings is designed with a more minimalist impression and still has the aesthetics of the beauty of the modern building. Modern architecture uses the concept of "forms follow function" by eliminating elements of ornamentation in buildings. The application of modern architecture in buildings is an adequate and practical approach in the form of a dormitory building. The methodology is mix method, namely, primary data from observations in the field at the design site and secondary data derived from informational data (literature) obtained from internet data sources such as journals, articles, and data in book references. This student dormitory research is expected to provide data for designing a building that can meet the needs of students on campus activities and students' daily lives and give comfort to its users.